PREDICTION OF SEDIMENT TRANSPORT DUE TO IRREGULAR WAVE MOTION - Taufiqur Rachman; Suntoyo Suntoyo (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
In general, waves in coastal environments are irregular and have a random shape with a height and period that was not constant. The accuracy of sediment transport rate prediction is the most important stages in the study of morphology and coastal marine environments. In addition, the predictive model of coastal morphology is more efficient to use the bottom shear stress calculation approach for practical purposes rather than a more complex approach to the modeling of two phases. In this paper, the calculation of sediment transport was based on the bottom shear stress modelling purposed with data validation from the experimental results in the turbulent bottom boundary layer over rough bed under irregular waves. The new approach to estimate the bottom shear stress was based on combining velocity and acceleration terms. Furthermore, a new approach of the bottom shear stress was applied to formulate the sheet flow sediment transport rate for irregular waves by using the experimental data from Dibadjnia and Watanabe (1998) and the empirical formula was found. Keywords: sediment transport, bottom shear stress, irregular waves